Compensatory Education for Disadvantaged Mexican Students: An Impact Evaluation Using Propensity Score Matching - Shapiro, Joseph; Trevino, Jorge Moreno (World Bank, Washington, D.C., 2013)
The authors use propensity score matching to evaluate the effectiveness of CONAFE, a compensatory education program in Mexico, in improving student test scores and lowering repetition and failure rates. They find that CONAFE is most effective in improving primary school math learning and secondary school Spanish learning. Secondary education delivered by way of television to remote communities and bilingual education for indigenous students are both shown to improve student achievement. CONAFE also lowers primary school repetition and failure rates. The authors conclude that this compensatory education program can effectively improve short-term learning results for disadvantaged students, but that improvement varies by the subject of instruction and the demographics of students taught.